Variations in Postprandial Blood Glucose Responses and Satiety after Intake of Three Types of Bread - Marianne S. H. Lunde; Victoria T. Hjellset; Gerd Holmboe-Ottesen; Arne T. Høstmark (Journal of Nutrition and Metabolism)
Background. The magnitude and duration of postprandial blood glucose (PPG) elevations are important risk factors of diabetes and coronary heart diseases. Aim. To study PPG after ingestion of breads with and without pea fibre and rapeseed oil. Methods. After fasting overnight, 10 Pakistani immigrant women participated in three experiments having a crossover design and involving ingestion of various types of bread: regular coarse bread or fibre enriched-bread with two levels of rapeseed oil, all providing 25 g available carbohydrates (CHO). Blood glucose and satiety were determined before the meal and every 15 min over the next 2 hours. Results. Intake of an amount of pea fibre-enriched bread containing 25 g CHO attenuated, the postprandial peak glucose value, the incremental area under the glucose versus time curve during 15 to 75 min, and the glycemic profile, and increased duration of satiety (𝑃<.05), as compared with intake of regular bread with 25 g carbohydrate. Conclusion. Pea fibre-enriched breads can reduce PPG and prolong satiety.